Grain market infrastructure in Kazakhstan and the possibilities of export development (Journal of Economic Research & Business Administration, 2016)
The article deals with the problem of limiting the increase in the vol-ume and expands the geography of Kazakh grain exports. The Republic has significant grain resources and during the years of independence entered the top ten world leaders in the export of grain. But the country can in-crease the supply of at least 50-60%, and enter the top five grain exporters. However, these plans are limited to a number of problems leading up be-ing the weak infrastructure of the grain market - from storage to the export of transport logistics. The state and the possibility of overcoming these limiting factors were the focus of this article.
Keywords: grain production; grain market; grain market infrastruc-ture; grain export.